Penggunaan Media Audiovisual Untuk Meningkatkan Hasil Belajar Siswa Pada Pembelajaran Seni Tari Di SMP Negeri 15 Padang - Yulia Suarty; Yuliasma Yuliasma; Susmiarti Susmiarti (SENDRATASIK UNP, 2019)
This article aimed to explain and describe about the students’ improvement in dance learning outcomes using audiovisual media in class VIII. 6 SMP Negeri 15 Padang. type of this research was classroom action research which was conducted as much as 2 cycles. The subjects of the research were the students in grade VIII. 6 SMP Negeri 15 Padang which amounted to 32 people. The data were collected by using observation sheets, the results of the knowledge tests (cognitive) and skills (Psychomotor) as well as documentation for the research. The results of this research showed that learning the art of dance using Audiovisual media succeeded to improve the learning outcomes of students in class VIII. 6 SMP Negeri 15 Padang. This was evidenced on improving students’ activities and student learning outcomes on cycle I and cycle II which increased primely. On cycle I, the overall student activities were 45,30%, while on cycle II, it had risen to 82,26 The overall of students’ learning outcomes on cycle 1 was 64.06, meanwhile on cycle II, student learning outcomes had risen to 83.68. Thus, the use of audiovisual media to enhance the outcomes in dance learning in class VIII. 6 SMP Negeri 15 Padang already has already achieved very well.